PENGARUH KEBIJAKAN HUTANG, KEBIJAKAN DIVIDEN, ASIMETRI INFORMASI DAN PROFITABILITAS TERHADAP PROBABILITAS PERTUMBUHAN PERUSAHAAN - ARYA PRADIPTA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
This study aimed to examine the effect of debt policy, dividend policy, information asymmetry and profitability on the probability that the company's growth proxy by the investment opportunity set. The Company will be classified in the company grows and the company does not grow by factor analysis of the investment opportunity set is calculated for each company. A statistical technique used in this study is a statistical technique logistic regression. Sample of firms drawn from companies listed in Indonesia Stock Exchange. The sampling technique used was purposive sampling judgmental. The results showed that the bid-ask spread, Debt Equity Ratio and Dividend Payout ratio does not significantly affect the probability of the company's growth. While the Return on Asset and Dividend Yield significantly affects the probability of firm growth.